Fall Prevention: Home Safety lnventory - Linda B. Bobroff (EDIS)
Most falls occur in the home, so it is wise to take time to do a home safety inventory. This 2-page fact sheet is a major revision that can be used to identify problem areas in your home. Written by Linda B. Bobroff, and published by the UF Department of Family, Youth and Community Sciences, July 2016.